Maternal and Perinatal Determinants of Late Hospital Discharge Among Late Preterm Infants; A 5-Year Cross-Sectional Analysis - Khasawneh, Wasim; Alyousef, Rahaf; Akawi, Zuhour; Al-Dhoon, Areen; Odat, Ahlam (Frontiers in Pediatrics, 2021)
Background: Although late preterm infants (LPIs) account for the majority of preterm births, they are mistakenly labeled and treated as “near term”. Whether longer initial hospital stay improves their outcomes and lowers readmission is controversial. The aim of this study is to identify maternal and perinatal factors associated with longer hospital stays and to assess the rate of readmission. Methods: The medical records of LPIs delivered at an academic center in Jordan over a 5-year period were reviewed. They were divided according to their initial hospital stay into the Early discharge group (ED, ≤ 3 days) and the late discharge group (LD, ˃ 3 days). Maternal and perinatal factors associated with ˃ 3-day hospital stay were reported. The rate of readmission was compared between both groups. Results: 2236 LPIs were included in the analysis representing 13% of total births and 81% of premature births. LD group constituted 54%. 1243 (56%) required admission to NICU. Factors associated with longer hospital stay included maternal prolonged rupture of membranes (AOR 1.9, 95% C.I 1.5, 2.4), C-section delivery (AOR 2.4, 95% C.I 1.9, 3), ˂ 35-week gestation (AOR 3.8, 95% C.I 2.6, 5), small-for-gestational-age (AOR 1.9, 95% C.I 1.1, 3.8), birthweight < 2500 grams (AOR 1.3, 95% C.I 1.1, 1.6), NICU admission (AOR 6.3, 95% C.I 3.4, 11.5), surfactant therapy (AOR 5, 95% C.I 2, 13.5), use of CPAP (AOR 1.7, 95% C.I 1.2, 2.2), jaundice (AOR 11.2, 95% C.I 7.7, 16.2), and sepsis (AOR 10.3, 95% C.I 4.8, 22). The readmission rate was 19% among the LD group and 13% among the ED group. Conclusion: LPIs are at high risk for developing prematurity-related morbidities and the duration of their initial hospital stay can be anticipated based on certain predisposing maternal and perinatal factors. Late discharge of LPIs does not lower the rate of readmission